Pengembangan Media Kartu Kuartet Digestiar untuk Meningkatkan Hasil Belajar Peserta Didik - Tia Tia; Moh. Fathurrahman (Paedagogie, 2026)
This study aims to design and evaluate the effectiveness of the Digestiar quartet card learning media based on Augmented Reality/AR on the human digestive system material for fifth grade elementary school students. The method used is Research and Development R&D with the Borg and Gall model which is implemented up to eight stages of development. The research subjects consisted of sixth grade students in the small-scale trial stage and fifth grade students in the usage trial stage carried out at SD Negeri 01 Jemowo, Boyolali Regency. Data collection was carried out through test techniques in the form of pretests and posttests, as well as non-test techniques including, observation, interviews, needs analysis questionnaires and response questionnaires. The data obtained were analyzed using normality tests, t-tests, and N-gain tests to determine the level of effectiveness of the learning media. The results showed that the Digestiar media obtained the "Very Appropriate" category based on the assessment of material experts with a percentage of 91% and media experts at 100%. The results of the normality test showed that the data were normally distributed, the t-test showed a significant difference between the pretest and posttest results, and the N-gain value was in the range of 0.30 < g < 0.70 which was included in the “Fairly Effective” category. The teacher's response showed a percentage of 90% and the student's response was 83.2%, both of which were included in the "Very Appropriate" category. Thus, the Digestiar quartet card media was declared "Quite Effective" and "Appropriate" for use in the learning process.